Spider-Man. Vol. 1, Miles Morales - Bendis, Brian Michael (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2016)
"Miles Morales is hitting the big time! Not only is he joining the Marvel Universe, but he's also a card-carrying Avenger, rubbing shoulders with the likes of Iron Man, Thor, and Captain America! And he'll soon be a media sensation in this All-New, All-Different New York. One thing's the same, though: non-stop action! Like when Earth's Mightiest heroes all fall, and Miles stands alone against a villain with the power to destroy the universe. Or when the Black Cat tries to get her claws in this new Spider-Man. Or when a new mutant threatens to grab the spotlight! And don't forget Miles' toughest foe yet: his grandmother! But his grades might be the ultimate challenge -- so maybe a study session (date?) with Ms. Marvel will help? Welcome to the neighborhood, Spider-Man -- hope it's friendly!" -- Page 4 of cover.